Alteration of Cholesterol Metabolism by Metformin Is Associated With Improved Outcome in Type II Diabetic Patients With Diffuse Large B-Cell Lymphoma - Jiang, Xiang-Nan; Zhang, Yan; Wang, Wei-Ge; Sheng, Dong; Zhou, Xiao-Yan; Li, Xiao-Qiu (Frontiers in Oncology, 2021)
Recent studies have demonstrated the benefits of metformin on patients with lymphomas. B-cell receptor (BCR)-PI3K-AKT pathway-dependent cholesterol synthesis may represent a positive feedback mechanism responsible for the pathogenesis of BCR-dependent diffuse large B-cell lymphomas (DLBCLs). Thus, restriction of lipid synthesis would affect the integrity of lipid-forming membranes and block the BCR signaling pathway. Our in vitro findings suggested that the blocking effect of metformin on BCR signaling pathway is possibly exerted via blocking the biosynthesis of cholesterol. A retrospective case-control study was subsequently conducted on type II diabetic patients with DLBCL who were on metformin. Metformin was identified to be associated with improved response rate and PFS in diabetic patients and appeared to be an effective therapeutic drug against DLBCL.